ANALISIS PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA DINI YANG BERMAIN GAWAI - Ellen Prima (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2021)
This study aims to analyze gross motor development in early childhood playing gadgets. The method used in this study is a phenomenological qualitative approach with data collection techniques such as observation and interviews. The subjects of this study were four men and women. The results of this study were the gross motor development of the research subjects varied with their respective characteristics. The gross motor development of subject R is appropriate for their age, subject M and N are quite appropriate for their age, while subject S is less suitable for their age.